Challenges in Education - Policies, Practice and Research - Clipa, Otilia (Erziehungskonzeptionen und Praxis / Educational Concepts and Practice, 2021)
This book contains ten state-of-the-art articles about current challenges in education. They go back to the international conference "Teacher Education for Promoting Well-Being in Schools" (S,tefan cel Mare University of Suceava / Romania, July 2020), organized by the Association for Teacher Education in Europe. The articles are concerned with the following: diversity in special education; research through photovoice; sentiments, attitudes and concerns about inclusive education of pre-primary education students; teacher education; new trends in education; influence of the COVID 19 pandemic on education; digital competences of teachers.